Democratic Social Practice and the Emergence of Social Work in China: A Call for Dialogical Engagement - McNicoll, Paule; Yan, Miu (Nouvelles pratiques sociales)

(untitled) (Université du Québec à Montréal, 2009)
The paper contrasts the conference focus on the democratic renewal of social practices, an internal process particular to the European and North-American contexts, with the development of social practices in China, where both external and internal forces influence social workers’ dealings with democratization and indigenization of well-established Western concepts. The goals of the authors are to problematize the questions of democratic renewal and to promote international communication among social practitioners.